Identification of a novel type of silk protein and regulation of its expression - Zurovec, M; Yang, C; Kodrík, D; Sehnal, F (The Journal of biological chemistry, 1998)
The silk of lepidopteran insects has been studied extensively as proteins of two categories: the fibroins, which are produced in the posterior section of silk glands, and the sericins, which are secreted in the middle section. We now describe a third category that is named seroins to accentuate the fact that both the sericin- and the fibroin-producing cells participate in seroin secretion. Using a probe derived from the N-terminal sequences of a 23-kDa components of Galleria mellonella silk, we isolated silk gland-specific cDNA encoding 167 amino acids, of which 17 constitute the signal peptide. The following 14 residues match the N-terminal sequences of the 23- and 22.5-kDa silk proteines. The reaction of these proteins with concanavalin A and the presence of two glycosylation sites in the seroin peptide sequence indicate that seroin is secreted in two forms that both contain a mannose-rich sugar moiety. Seroin is distinguished from other silk proteins by high proline content (34 residues or 20.26% by weight), lack of cysteines, and the presence of two kinds of short amino acid repeats. The seroin gene is expressed in both the posterior and middle silk gland sections. The expression fluctuates during development in correlation with the feeding regime and the changes in hormone titers: seroin mRNA is high in the silk glands of feeding larvae, declines at ecdysis, reaches a maximum during cocoon spinning, and thereafter rapidly drops to an undetectable level. In vivo and in vitro experiments showed that the drop is caused by ecdysteroid hormones and is prevented by juvenile hormones. N-terminal sequencing of several silk proteins of Bombyx mori revealed that the 8- and 13-kDa proteins share 5 or 6 out of 10 identified amino acids with the N terminus of Galleria seroin and obviously represent seroin homologues. The result suggests that seroin-type proteins are a general component of lepidopteran silk.
Keywords: molekulární sekvence - údaje; messenger RNA; Ecdysteroids; Juvenile Hormones; juvenilní hormony; RNA, Messenger; steroidy; Bombyx; Base Sequence; můry; vývojová regulace genové exprese; Steroids; Moths; sekvence aminokyselin; komplementární DNA; glykoproteiny; Amino Acid Sequence; bourec; ekdysteroidy; otevřené čtecí rámce; Molecular Sequence Data; DNA, Complementary; Gene Expression Regulation, Developmental; Glycoproteins; Molecular Weight; Open Reading Frames; Animals; hmyzí proteiny; sekvence nukleotidů; Insect Proteins; zvířata; molekulová hmotnost